2021
DOI: 10.3389/fpls.2021.665745
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Mapping of Mixed Linkage (1,3;1,4)-β-Glucan and Starch Contents in Rice Whole Grain

Abstract: The glucan content of rice is a key factor defining its nutritional and economic value. Starch and its derivatives have many industrial applications such as in fuel and material production. Non-starch glucans such as (1,3;1,4)-β-D-glucan (mixed-linkage β-glucan, MLG) have many benefits in human health, including lowering cholesterol, boosting the immune system, and modulating the gut microbiome. In this study, the genetic variability of MLG and starch contents were analyzed in rice (Oryza sativa L.) whole grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 111 publications
1
4
0
Order By: Relevance
“…Comparison of the locations of the detected genomic regions in this study (QTLs) and the known reported QTLs for grain yield and other related traits are represented in Supplemental Table S2. Notably, a number of QTLs for arabinose, xylose, fucose, galactose, and rhamnose contents were mapped in the same genomic regions that were identified in our earlier report on starch and (1,3;1,4)-β-glucan contents in RWG (Panahabadi et al, 2021).…”
Section: Marker-trait Association Analysissupporting
confidence: 56%
See 2 more Smart Citations
“…Comparison of the locations of the detected genomic regions in this study (QTLs) and the known reported QTLs for grain yield and other related traits are represented in Supplemental Table S2. Notably, a number of QTLs for arabinose, xylose, fucose, galactose, and rhamnose contents were mapped in the same genomic regions that were identified in our earlier report on starch and (1,3;1,4)-β-glucan contents in RWG (Panahabadi et al, 2021).…”
Section: Marker-trait Association Analysissupporting
confidence: 56%
“…The studied plant panel consisted of 197 rice accessions collected from 70 countries (Supplemental Table S1). The grains from these accessions were previously analyzed in another GWAS project to understand the genetic control of starch and (1,3;1,4)‐β‐glucan content in grain (Panahabadi et al., 2021) and cellulose, lignin, and fermentable sugars in rice straw (Panahabadi et al., 2022). Our new analyses present major monosaccharides composition (including arabinose, xylose, mannose, galactose, fucose, and rhamnose) in whole grain of the same accessions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro‐checker software was used to check scoring errors, stutter, or null alleles (Van Oosterhout et al, 2004 ). Gametic disequilibrium between all pairs of microsatellite loci was tested using POPGENE (Version: 1.32; Panahabadi et al, 2021 , 2022 ; Yeh Francis et al, 1999 ). Null alleles and deviations from Hardy–Weinberg equilibrium for each locus were estimated using Genepop (Version 4.2.1; Panhabadi et al, 2022 ; Rousset, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…A genome-wide association study (GWAS) is considered an attractive approach for assessing grain quality. Starch contents and starch-related parameters in rice were studies using GWAS analysis [162,163]. Recently, GWAS was performed to identify genetic factors of wheat grain quality including grain protein content, grain starch content, and grain hardness [164].…”
Section: Molecular Marker Development and Application For Wheat Starchmentioning
confidence: 99%